Serum low-density lipoprotein levels, statin use, and cognition in patients with coronary artery disease - Rej S (Dove Medical Press, 2016)
Soham Rej,1 Mahwesh Saleem,2,3 Nathan Herrmann,1,3 Anthi Stefatos,4 Allison Rau,3 Krista L Lanctôt1–3 1Department of Psychiatry, 2Department of Pharmacology and Toxicology, University of Toronto, 3Neuropsychopharmacology Research Group, Sunnybrook Health Sciences Centre, Toronto, ON, 4Faculty of Medicine, Université de Montréal, Montréal, QC, Canada Aim: Statins have been associated with decreased cognition due to the effects of low concentrations of low-density lipoprotein (LDL) on brain function. This has remained controversial and is particularly relevant to patients with coronary artery disease (CAD), who have an increased risk of cognitive decline and are frequently prescribed statins. This study hypothesized that low concentration of LDL is associated with poor cognition in CAD patients using statins. It also explored the association between high-dose versus low-dose statins on cognition in this population. Patients and methods: Baseline cross-sectional data from a longitudinal study of 120 statin-using CAD patients were examined (mean statin duration 25±43 months). The main outcomes were measures of global cognition and cognitive domains, with poor cognition defined as cognitive performance ≤1 standard deviation below the population age and education adjusted means. A battery of cognitive tests was used to assess verbal memory, executive function, speed of processing, visuospatial memory, and global cognition. Adjusting for age, sex, education, and other covariates, multivariable logistic regression analyses assessed associations between low LDL levels (<1.5 mmol/L), statin use, and poor cognition. Results: LDL levels were not associated with global cognition or individual cognitive domains. High-dose statin use was associated with higher visuospatial memory (odds ratio, OR [95% confidence interval, CI] =0.12 [0.02–0.66], P=0.01) and executive functioning (OR =0.25 [0.06–0.99], P=0.05). This effect was independent of covariates such as LDL levels. Conclusion: Low LDL levels do not appear to be associated with poor cognition in CAD patients using statins. Whether high-dose statin use may have positive effects on cognition in CAD patients could be investigated in future studies. Keywords: cholesterol, visuospatial cognition, heart disease, psychopharmacology, adverse drug events